Characterization and evaluation of Metal Oxide Electrodes supported on Titanium for the Electrooxidation of Cyanide in aqueous medium - La Rosa Toro G., A. (2003)
In this work the electrochemical behaviour of the electrodes of SnO₂ doped withantimony and also with antimony and platinum has been studied. A Co,O, electrodehas been also analysed all of them supported on a titanium substrate for its use in the electrooxidation of cyanide The electrodes were characterised by Scanning Electron Microscopy (SEM), EDX microanalysis and cyclic voltametry. The service life of the electrodes has been evaluated in galvanostatic conditions at 100 mA/cm². The electrooxidation of cyanide was performed in a filter press cell using current densities of 5 and 25 mA/cm².